Pendampingan Pembelajaran Kosakata Bahasa Inggris Bagi Siswa SD 2 Panjang Kudus dengan Permainan Guessing Games - Sri Endang Kusmaryati; Slamet Utomo; Titis Sulistyowati (Universitas Muria Kudus, 2019)
Teaching English for elementary school students aims to introduce English as a language to communicate. In this case, teachers should find ways of delivering English materials easily and how to make something difficult to be interesting and challenging to learn. Playing games is one of the interesting ways in the learning process for early childhood. Through the game, knowledge and skills are delivered in a relaxed manner. This will make the classroom atmosphere fun, so it is expected to generate the spirit of learning for them. Elementary school students as early age learners should be given the opportunity to play and have fun as well as learning, so that knowledge is given in a fun way will be easily absorbed. The purpose of community service is to provide English language teaching assistance for elementary students using Guessing games. This activity is expected that students can learn with fun by using interactive games, so that learning will be more interesting and fun, and expected the students will master the English well.